Global Working Hours - Gethin, Amory; Saez, Emmanuel (Quarterly Journal of Economics, 2026)
Abstract This article uses labor force surveys from 160 countries to build a new microdatabase on hours worked covering 97% of the world population in cross section. We also construct time series spanning over 20 years in 86 countries. Hours worked per adult slightly decline with GDP per capita but are weakly correlated with development overall. Hours worked by the young (aged 15–19) and elderly (aged 60+) fall with development, driven entirely by growing school attendance and public pension coverage. Hours worked among prime-age adults (aged 20–59) are stable with development but undergo a great gender reshuffling: falling hours per male worker have been exactly offset by increases in female labor force participation in many countries. Labor income taxes are strongly negatively related to hours worked across countries. This correlation is attenuated when controlling for social spending and disappears when further controlling for working hours regulations. Both social spending and working hours regulations are associated with lower hours worked.